The Influence of Leadership Style and Organizational Culture on Employee Performance at the Cirebon District Health Office - Rosa Huzaenifah Fashihatun; Dharliana Hardjiwikarto; Juwita (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of leadership style and organizational culture on employee performance at the Cirebon District Health Office. The high demand for healthcare services, driven by a large population and an increase in infectious disease cases, necessitates optimal employee performance. Therefore, effective human resource management is required through the implementation of appropriate leadership and a robust organizational culture. This research employs a quantitative approach using a survey method. Data were collected by distributing questionnaires to employees of the Cirebon District Health Office, selected through specific sampling techniques. Data analysis was conducted using multiple linear regression with the assistance of statistical software. The results indicate that leadership style has a positive influence on employee performance. Organizational culture also has a positive and significant impact on employee performance. Simultaneously, leadership style and organizational culture significantly influence employee performance. These findings suggest that improving leadership quality and strengthening organizational culture can serve as vital strategies for enhancing employee productivity and professionalism. This research provides a theoretical contribution to the development of human resource management studies in the public sector, specifically within the healthcare field. Practically, the results of this study are expected to serve as a foundation for leadership in formulating more effective human resource management policies oriented toward improving the quality of public services.